Hospital at home treatment with remdesivir for patients with COVID-19: real-life experience. (February 2023) - Pereta, Irene; Morancho, Alma; López, Néstor; Ibáñez, Begoña; Salas, Cristina; Moreno, Laura; Castells, Eva; Barta, Ariadna; Cubedo, Marta; Coloma, Emmanuel; Cardozo, Celia; García-Pouton, Nicole; et al.
HIGHLIGHTS: Remdesivir is recommended for hospitalized and nonhospitalized patients with COVID-19. Remdesivir treatment requires intravenous infusion hindering outpatient management. Infusion of Remdesivir at home may be a safe alternative. Hospital at home is a safe and efficient alternative for managing patients with COVID-19. Abstract: Objectives: Access and appropriateness of therapeutics for COVID-19 vary because of access or regulatory barriers, the severity of the disease, and for some therapies, the stage of the pandemic and circulating variants. Remdesivir has shown benefits in clinical recovery and is the treatment of choice for selected patients, both hospitalized and nonhospitalized, in main international guidelines. The use of remdesivir in alternatives to conventional hospitalization such as hospital at home (HaH) units remains incompletely explored. In this study, we aim to describe the real-life experience of outpatient remdesivir infusion for COVID-19 in a HaH unit. Methods: We selected all the consecutive patients receiving remdesivir from a prospective cohort of 507 COVID-19 patients admitted at a HaH unit. Admission criteria included COVID-19 with a fraction of inspired oxygen requirement under 0.35 and respiratory rate under 22 rpm. Patients were daily assessed in person by a nurse and a physician. Results: A total of 236 patients admitted at the HaH unit received remdesivir, 172 of whom were treated at home. Only 2% presented any adverse event related to the infusion, all of them mild. HaH saved 1416 day-beds, with only 5% of the patients requiring transfer back to the hospital. Conclusion: Remdesivir infusion in HaH units seems to be a safe and efficient alternative to conventional hospitalization for treating patients with nonsevere COVID-19.